2021
DOI: 10.1172/jci.insight.142577
|View full text |Cite
|
Sign up to set email alerts
|

GRHL3 activates FSCN1 to relax cell-cell adhesions between migrating keratinocytes during wound reepithelialization

Abstract: The migrating keratinocyte wound front is required for skin wound closure. Despite significant advances in wound healing research, we do not fully understand the molecular mechanisms that orchestrate collective keratinocyte migration. Here, we show that, in the wound front, the epidermal transcription factor Grainyhead like-3 (GRHL3) mediates decreased expression of the adherens junction protein E-cadherin; this results in relaxed adhesions between suprabasal keratinocytes, thus promoting collective cell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…We speculate if downregulation of tight junction proteins combined with adherens junctions at the wound edge of human chronic wounds might contribute to the pathophysiology of the chronic wounds by impairing skin repair due to decreased migratory capacity of the epidermal cells as well as reduced barrier function. However, E‐cadherin expression has been found to be almost absent in the wound front in an acute wound model using human skin xenograft (21). These observations are made in the wound front with intact epidermis, without any observations from the specific wound edge (transition from intact epidermis to loss of epidermal cells).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate if downregulation of tight junction proteins combined with adherens junctions at the wound edge of human chronic wounds might contribute to the pathophysiology of the chronic wounds by impairing skin repair due to decreased migratory capacity of the epidermal cells as well as reduced barrier function. However, E‐cadherin expression has been found to be almost absent in the wound front in an acute wound model using human skin xenograft (21). These observations are made in the wound front with intact epidermis, without any observations from the specific wound edge (transition from intact epidermis to loss of epidermal cells).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies of migrating epithelial cell sheets have shown that adherens junctions are essential for cells to migrate collectively (18), and that E-cadherin is tightly regulated in collective cell migration during embryonal development, tumor metastasis, and wound healing (19,20). In an acute wound model using human xenografts, a downregulation of E-cadherin is observed in the wound front (21). AQPs are pivotal players in collective cell migration and it is thought that the facilitated water permeability aids in cell shape changes required for cell migration in restricted 3D environments (22).…”
mentioning
confidence: 99%
“…The involvement of Piezo1 with components of the cytoskeleton is an area that remains to be fully explored. Damages observed after the topical application of Dooku1 on skin biopsies may be the results of the lower level of E-cadherin, weakening cell-cell adhesion and E-cadherin is implicated in wound healing modulation, as epithelial cells usually trigger their "migratory machinery" upon loss of adhesion to their neighbours [29]. Existing data describe Piezo1 as a "molecular brake" regarding wound closure, to ensure effective maintenance of epithelial integrity [30].…”
Section: Discussionmentioning
confidence: 99%
“…E‐cadherin is implicated in wound healing modulation, as epithelial cells usually trigger their “migratory machinery” upon loss of adhesion to their neighbours [29]. Existing data describe Piezo1 as a “molecular brake” regarding wound closure, to ensure effective maintenance of epithelial integrity [30].…”
Section: Discussionmentioning
confidence: 99%
“…102 Granulation tissue can simultaneously initiate macrophage polarization toward pro-restorative polarization, fibroblast proliferation and myofibroblast differentiation, followed by wound contraction, neointimal formation and matrix deposition. 103 Poor production of granulation tissue can lead to chronic healing or even non-healing of the wound; excessive deposition of granulation tissue, such as over-proliferation of fibroblasts and/or persistence of myofibroblasts in the granulation tissue can lead to scar formation, 104 At this point, phagocytes play a role in preventing excessive deposition of collagen fibers. It has been suggested that the "eat-me" signal CRT can promote the formation of traumatic granulation tissue.…”
Section: Granulation Tissue Generationmentioning
confidence: 99%